Pengaruh Zig-Zag Dribbling dan Wall Pass terhadap Kontrol Bola Futsal Siswa SMP Walisongo Sidoarjo - Maulidin, M. Dhandy; Muhammad Wahyono; Ramadhany Hananto Puriana (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aimed to analyze the effect of Zig-Zag Dribbling and Wall Pass training on improving futsal ball control among students of SMP Walisongo Sidoarjo. The research applied a quantitative approach using a true experimental randomized pretest–posttest two-group design. The sample consisted of 20 futsal extracurricular students who were randomly assigned into two treatment groups. Data were collected through ball control skill tests conducted during pretest and posttest sessions. Data analysis included descriptive statistics, normality testing, homogeneity testing, paired sample t-test, independent sample t-test, and analysis of covariance. The results showed that both training methods significantly improved ball control performance. The Zig-Zag Dribbling group demonstrated a higher mean improvement compared to the Wall Pass group. Analysis of covariance indicated a significant difference between groups after controlling initial ability, suggesting that Zig-Zag Dribbling training tends to be more effective in improving students’ ball control. These findings indicate that training emphasizing direction changes and ball-touch control while moving provides stronger stimulation for ball mastery. This study recommends that physical education teachers and futsal coaches integrate both training models in a structured program to enhance students’ fundamental technical skills